Formulasi dan evaluasi karakter fisik sediaan gel ekstrak etanol daun salam (Syzygium polyanthum) - Lalu Mukhlis Maqbul Sani; Windah Anugrah Subaidah; Yayuk Andayani (Sasambo Journal of Pharmacy, 2021)
Abstrak: Bay leaves (Syzygium polyanthum) are known to have antioxidant effects that can neutralize free radicals found in the skin. The objectives of this research are to formulate the ethanol extract of bay leaves into gel formulation and evaluate the physical properties of gel formulation. Ethanol extract of bay leaves was obtained through the maceration method with 70 % ethanol as a solvent. The thick ethanol extract of bay leaves was formulated into gel formulation with CMC – Na as a gelling agent, glycerin as a humectant, methyl paraben as a preservative, and aquadest as a solvent. After the freeze-thaw test was done, there was no change found in organoleptic but there were changes in pH, spreadability, and adhesion. The pH of gel preparation before being in storage was 5 and after being in storage was 6. In the spreadability, gel formulation spread 5,5 cm before being in the storage, and 5,1 cm after being in the storage. Gel adhesion has a sticky time of 8.35 seconds before in being storage and 8.45 seconds after being in storage.